EVOLUSI ADAM DALAM KAJIAN TAFSIR HADIS - Roswati Nurdin (IAIN Ambon, 2020)
The creation of Adam as the first human being is always associated with the theory of evolution that was coined by Charles Darwin who stated, that humans came from apes, had sued the meaning of human creation. The implication is that the theory of evolution shakes the joints of human belief (religion). Although the theory of evolution has been proven by various scientific discoveries, many religious scholars oppose the process of human evolution. This is based on information in the scriptures of each religion that says that Adam was the first human being. In the Qur'an, there are a number of verses that describe human creation starting from the initial process of creation, coming from the ground, then from that land, after going through a very long process, humans are formed. In the perspective of the traditions of creation Adam also expressed a lot. But in this case there is no question of the existence of Adam as the first human being but what will be criticized is the validity of the traditions that tell about Adam's creation. In the study of hadith, issues relating to the Prophet Adam as revolved around the creation of Adam with its prototype, the color of the soil as the raw material for the creation of Adam, the day of creation and the age of Adam. Keywords: creation, prototype, Adam